Biological Therapy for Inflammatory Bowel Disease 2020
DOI: 10.5772/intechopen.84375
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TNF in the Pathogenesis of Inflammatory Bowel Disease

Abstract: Tumor necrosis factor (TNF) is a pleotropic cytokine involved in a wide range of pathological processes, including inflammatory bowel disease (IBD). In the past, TNF was recognized as a pro-inflammatory cytokine with deleterious effects. This has led to the development of anti-TNF drugs, which revolutionized the treatment of inflammatory disorders such as Crohn's disease. However, in the past 20 years, clinical studies have shown that anti-TNF drugs are not always effective. Moreover, in some rare cases, anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Another key player in intestinal inflammation during IBD is the cytokine TNF-α [61]. Indeed, very high TNF-α levels are present in the gut mucosa of IBD patients and positively correlate with clinical disease severity, thus suggesting a negative contribution for TNF-α to the chronic intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Another key player in intestinal inflammation during IBD is the cytokine TNF-α [61]. Indeed, very high TNF-α levels are present in the gut mucosa of IBD patients and positively correlate with clinical disease severity, thus suggesting a negative contribution for TNF-α to the chronic intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…And, it put on more on risk during the combinational therapy [122]. Other than this other paradoxical side effects such as psoriasis/psoriasiform skin, development of sarcoidosis-like lesions, late occurrence of arthritis/synovitis and lupus-like syndrome (0.5 to 1% of patients) can also be developed [123][124][125][126][127]. Additionally, novel therapies including JAK inhibitor [128][129][130], anti-MAdCAM-1 [131][132][133][134][135], an anti-SMAD7 antisense oligonucleotide (mongersen) [136][137][138], S1P1 [128,139] and anti-interleukin (IL)-12/23 (ustekinumab) [140][141][142][143][144][145][146] have been under investigation for safety and other purposes.…”
Section: Therapeutic Role Of Tregs In Ibdmentioning
confidence: 99%
“…APP has shown strong links to Alzheimer's disease, but research also suggests that APP may influence susceptibility towards gut inflammatory diseases [61]. Evidence showing a link between TNF and IBD have been reported in previous publications in which IBD-patients showed increased levels of TNF in their serum samples [62]. Additionally, the metabolites-cyclic AMP and nitric oxide-appear to be a major contributor to many sub-networks in this third network, with direct links to both APP and TNF.…”
Section: Uibd Networkmentioning
confidence: 93%
“…5h) includes metabolites that interact with TNF and MYC protein complexes. Previous findings suggest that IBD-patients show increased levels of TNF in their serum samples [62]. As for the effect of MYC in CD, it has been found that in active CDpatients, the down-expression of c-MYC in patients' epithelium may result in attenuated cell proliferation, which therefore suggest that it could contribute to mucosal ulceration [69].…”
Section: Networkmentioning
confidence: 99%